Morphological diversification of female judo athletes - Jagiello, W.; Kalina, R.; Korobielnikow, G. (Archives of Budo, 2007)
Study aim: Cognitive purpose of the research is an attempt of defi ning morphological diversifi cation of Polish female representatives in judo with regard to weight categories. Material/methods: The research included female representatives of Poland in judo (n=13). Age of the tested ranged from 18 to 19 years. Anthropometric measurements were conducted during grouping of the national team. All together 20 basic somatic features were measured. The results of the measurement underwent basic statistic analysis. Results: In result of the conducted research characteristic features of body build of female judo competitors of various weight categories were revealed and internal proportions of factors of body build were determined. Conclusions: The important factor determining morphological diversifi cation of female judo competitors are weight categories. Female judo competitors of heavy categories are characterized fi rst of all by bigger body build. Body build of female competitors of middle weight categories is the most similar to comparative group. Female competitors of light categories are characterized by generally smaller body build. Proportions of external features show, that in all weight categories particularly strong muscles are on forearm and weak on shin.